Socrates on Philosophy and Politics: Ancient and Contemporary Interpretations (2012)
Socrates can be said to have left the subsequent philosophical tradition with the problem of the relation between philosophy and politics. Already in the Republic the proposal of philosopher-kings represents more a tension than an identity. While Aristotle responds by insisting on a sharp distinction between politics and philosophical wisdom, this distinction proves on closer examination much less sharp than might appear. Heidegger characterizes philosophy as the only authentic politics and the philosopher as ruling just by virtue of being a philosopher. In contrast, Foucault insists that, if philosophy can play a role in relation to politics by transforming the subject who lives politically, it plays no role within politics. In this contrast can be seen the ‘fallout’ of the tension bequeathed by Socrates through both Plato and Aristotle.